2021
DOI: 10.1292/jvms.20-0505
|View full text |Cite
|
Sign up to set email alerts
|

Detection of <i>Mycoplasma wenyonii</i> and “<i>Candidatus</i> Mycoplasma haemobos” from Japanese Black breeding cows in Kyushu and Okinawa region, southern part of Japan

Abstract: This study aimed to elucidate the epidemiological status of hemoplasma infection and investigate the interaction between Theileria orientalis and hemoplasmas in Japanese Black breeding cows raised in the Kyushu and Okinawa regions. Blood samples were collected from 400 cows from 80 different farms in eight prefectures (five samples per farm and 10 farms per prefecture). Mycoplasma wenyonii (Mw), "Candidatus Mycoplasma haemobos" (CMh), and T. orientalis were examined by polymerase chain reaction (PCR) assay usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…Interestingly, the finding of the two hemotropic Mycoplasma spp. ; M. wenyonii and 'Candidatus M. haemobos' as single or co-infection in the cattle populations examined in this study is similar to reports from different parts of the world [16][17][18][19]36]. These findings underscore the ubiquitous nature of these organisms in cattle.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Interestingly, the finding of the two hemotropic Mycoplasma spp. ; M. wenyonii and 'Candidatus M. haemobos' as single or co-infection in the cattle populations examined in this study is similar to reports from different parts of the world [16][17][18][19]36]. These findings underscore the ubiquitous nature of these organisms in cattle.…”
Section: Discussionsupporting
confidence: 87%
“…Elsewhere, higher prevalence than the results from this study were also reported. For example, the prevalence of 32.2% in Cuba [16], 28.6% in the Philippines [36], 64.2% in Brazil [19] and >90% in Japan and USA [17,18]. The variations in prevalence may be due to differences in laboratory procedures, climatic conditions, study population characteristics and sampling methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall prevalence of hemoplasmas in this study was 33.7%, which was higher than we anticipated. Our results are similar to those from Brazil (34.83%) [ 6 ], Uganda (32.2%) [ 31 ], and Turkey (31.64%) [ 29 ], but were markedly lower than those reported in the Philippines [ 11 ], Cuba [ 21 ], Germany [ 18 ], Japan [ 26 ], Nigeria [ 32 ], and Switzerland [ 33 ]. According to our results, the infection rates of M. wenyonii and C. M. haemobos were 20.2% and 3.8%, respectively, suggesting that M. wenyonii is more prevalent in Korean native cattle than C. M. haemobos .…”
Section: Discussionsupporting
confidence: 86%
“…Hemoplasmas have constantly been detected in cattle in the last few years [ 32 , 33 , 34 , 35 , 36 ]. However, their transmission by ticks lacks evidence.…”
Section: Discussionmentioning
confidence: 99%